DAMPAK IMPELEMENTASI SISTEM INFORMASI AKADEMIK TERHADAP KEPUASAN MAHASISWA (STUDI PADA INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA) - Dwitayanti, Yevi (Jurnal Manajemen dan Keuangan, 2011)
The study aims at testing empirically the effect of implementation of academic information system on studentsâ satisfaction. Dependent variable in this research is sStudentsâ satisfaction is a while implementation of academic information system is independent one.The data are collected by questionaires to the respondents. They are second grade students of IBI Darmajaya in 2010/2011 academic year. The sample is taken by Proportional random sampling method. Based on the method, we get 197 questionaires. A simple linear regression is employed as analitical technic. It is applied by using 17th SPSS.The result shows that implementation of academic information system has possitive effect on studentsâ satisfaction. This conclusion support the prediction of many previous researches. This indicates that the model used is not proper because the model is built on the construct of implementation of academic information system on studentsâ satisfaction.Keywords : implementation of cademic information system, students satisfaction